Analisis Kesalahan Penulisan Terhadap Penggunaan Tanda Baca dalam Karangan Narasi Siswa Kelas IV SD Negeri Manjalling Kabupaten Gowa - Rista Nuraidah Subair; Andi Adam; Rahmatiah Rahmatiah (Lembaga Pengembangan Kinerja Dosen, 2024)
The main problem in this study is how the writing errors in the use of punctuation marks, commas, hyphens, exclamation marks and quotation marks in narrative compositions in Class IV of Manjalling State Elementary School and And aims to find out how the errors in the use of punctuation in students' narrative compositions totaling 12 student narrative compositions. This type of research is descriptive qualitative research. The data and data sources in this study are narrative essays of grade IV students of Manjalling Elementary School, Gowa Regency. The instruments used in this study were observation, interviews, and data from students' narrative essays. The results of the study showed that the results of the essays analyzed using descriptive analysis were still found to contain errors in the use of punctuation. This can be seen in the percentage of errors in the use of period punctuation 35.13%, comma punctuation 48.65%, exclamation punctuation 2.70%, hyphen 8.10%, and quotation marks 5.40%. Based on the results of the study, it can be concluded that there are still errors in writing regarding the use of punctuation in students' narrative essays, especially in the use of periods and commas.